Barriers Affecting Successful Integration of ICT in Moroccan Universities - Youssouf Laabidi; Hicham Laabidi (Yayasan Visi Intan Permata, 2016)
The implementation of technology in classrooms affords educators more opportunities to work better in their lessons. However, there are numerous distinctive barriers that might prevent teachers from making use of Information and Communication Technology (ICT) in their teaching practices. Admittedly, studying the obstacles to the integration of technology in schools would be an important step in developing the quality of teaching. The primary objective of this study is to discover the barriers that stop university language teachers from using ICT in teaching. In this study the questionnaire is employed as data collection instrument. The questionnaire addresses only university English language teachers. Forty-six university English language teachers are chosen from two universities: Moulay Ismail University Faculty of Arts and Humanities – Meknes and Sidi Mohamed Ben AbdellahDahr – El Mahraz – Fes as a case study. So as to analyze the data from the questionnaire, the Statistical Package for Social Sciences (SPSS) version 19 is employed. The research findings reveal that Moroccan university English language teachers face multiple barriers such as large classes, lack of computers, lack of Internet and insufficient technical support that prevent them from using ICT in their teaching practices.